VASYL’ NIMCHUK – THE RESEARCHER OF PAMVO BERYNDA’S “SLOVENOROS’KYI LEXICON” (ON THE 390th ANNIVERSARY OF PUBLISHING “THE LEXICON” AND THE 85th ANNIVERSARY OF VASYL’ NIMCHUK’S BIRTHDAY) - Greshchuk, V. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article analyses the role of V. V. Nimchuk in the research of Pamvo Berynda’s “Slovenoros’kyi Lexicon”. At the end of the 50s of the previous century the researcher prepares the mentioned dictionary for a reissue and in 1961 he has it published with his extensive foreword, where he generalized scarce biographical data about the lexicographer and performed detailed characteristics of “The Lexicon”. The dictionary’s characteristics contain the data about the history of its creation, the source base, structure and character of the dictionary entries and the employment of it in a further lexicographic practice. In other publications by V. V. Nimchuk, dedicated to P. Berynda’s “Lexicon”, the scholar developed and deepened the thoughts, expressed in his preface to the dictionary.